Evaluating the Impact of Solar-Powered Robots on Agricultural Practices - Madhuri R. Metkar; Adarsh D. Ovhal; Suraj B. Jagtap; Pratiksha N. Salunke; Minakshi L. Jadhav (International Journal of Advanced Control and System Engineering, 2023)
Agriculture is the principal occupation of more than 40% of the global population. The primary goal of this article is to create an agricultural multifunctional vehicle that might operate automatically. It is intended to reduce the load of work for farmers which speeds up and improves the quality of the work. The use of automated multitasking solar-powered agriculture robots is a novel way to increase agricultural productivity while reducing the demand for human labour. In India, agriculture provides a living for around 70% of the population. These days, applying pesticides, water, and seeds are challenging tasks. To prevent pest and weed attacks in the field, the robot sprays pesticides, and weedicides. The solar panel that is mounted above the car can also be used to recharge the battery. The equipment required for the operations is pricy and cumbersome to operate. Therefore, by creating a system that will require less manpower and time, the agricultural system in India should be develop. This system guarantees the use of environmentally acceptable energy sources and reduces the need for frequent vehicle charging. In this study solar-powered automated multitasking agriculture robots provide farmers with a practical and sustainable option to increase output and lessen their environmental impact.
Keywords: Agriculture; Automation; Robot; Solar Panel; microcontrollers; pesticide spraying; seed sowing; water sprinkling